ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI EFFECTIVE TAX RATE PADA PERUSAHAAN AUTOMOTIVE AND ALLIED PRODUCTS YANG TERDAFTAR DI BURSA EFEK INDONESIA - Winarsih, 13.05.52.0256; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2016)
This study aimed to examine the effect of institutional ownership structure, the audit committee, audit quality, independent board, the number of commissioners and the size of the company to the effective tax rate on Automotive Company Listed on the Stock Exchange Year 2010-2014. automotive companies listed in Indonesia Stock Exchange in the period 2010- 2014. The population in this study is the automotive company which is listed on the Indonesia Stock Exchange in the period from 2010 to 2014. The sample in this study as many as 11 companies. The sampling technique used purposive sampling. The criteria for the sample in this study is the use Rupiah company. The analysis tool used is multiple linear. Results of the analysis can be concluded that: Institutional Ownership structure proved to be significant and have a negative direction of the effective tax rate. Audit committee proved to be significant and have a positive direction towards the effective tax rate. Audit quality proved to be significant and have a positive direction towards the effective tax rate. BOC Independent proved significant and has a positive direction towards the effective tax rate. Number of BOC proved to be significant and have a negative direction of the effective tax rate. Company size proved to be significant and have a negative direction of the effective tax rate.Keywords: Institutional Ownership Structure, The Audit Committee, Audit Quality, Independent Board, The Number Of Commissioners, The Size Of The Company, The Effective Tax Rate